Depresión y su efecto en el desarrollo psicosocial de una adulta de 30 años de edad en época de pandemia por covid-19 en la ciudad de Babahoyo - Ramírez Varas, Lissette Mariuxi (2023)
The present case study was carried out with the objective of analyzing whether the depression disorder influences the psychosocial development of a 30-year-old adult during the COVID-19 pandemic in the city of Babahoyo. All this was carried out through the use of clinical history, semi-structured interview, direct observation, and the application of psychological tests "Beck Depression Inventory", "Hamilton Anxiety Scale" and the "record of thoughts and emotions of the CBT”. In addition, a qualitative methodology was incorporated, which was directed to study the dependent and independent variables, on the other hand, thanks to the implementation of the CBT techniques, it was possible to fulfill the initially stated objective, in the same way through a therapeutic plan. managed to modify those thoughts that the patient expressed during the psychological intervention, thus managing to mitigate the emotional and behavioral problems of the patient due to the depression disorder in times of the COVID-19 pandemic, finally it is concluded that the results obtained were the which were aimed at improving their quality of life, both personal and social.